Penegakan Hukum Dalam Mengadili Anggota Militer Yang Melakukan Tindak Pidana Umum - Arief Fahmi Lubis (Universitas 17 Agustus 1945 Semarang, Indonesia, 2021)
The penalties imposed on TNI soldiers are actually more severe than those imposed in general courts. The punishment imposed on TNI soldiers is not only limited to imprisonment or fines, but sometimes serious criminal offenders are often given additional punishment in the form of dishonorable discharge (PDTH) from military service. The aim of this research is to show that for legal subjects who have military status, the role of superiors who have the right to punish or what is known as Ankum is very dominant. Military members who are involved in criminal acts are subject to two inherent penalties, namely first, in the form of disciplinary penalties which are imposed in the form of penalties for delaying promotion, demotion or even dismissal. This research is qualitative which uses a descriptive approach to collect data systematically, factually and quickly according to the description when the research was carried out. The results of this research show that the determination of absolute competence based on the emphasis on the consequences of losses incurred can be said to be in line with what is stated in Article 3 paragraph (4) letter a of TAP MRP Number VII of 2000 concerning the Role of the Indonesian National Army and the Role of the Republic of Indonesia's National Police. Indonesia which states that